Design Patterns for e-Science - Gardner, Henry; Manduchi, Gabriele (Texts in Computational Science and Engineering, 2007)
This is a book about a code and about coding. The code is a case study which has been used to teachcourses in e-Science atthe Australian NationalUniv- sity since 2001. Students learn advanced programming skills and techniques TM in the Java language. Above all, they learn to apply useful object-oriented design patterns as they progressively refactor and enhance the software. We think our case study,EScope, is as close to real life as you can get! It is a smaller version of a networked, graphical, waveform browser which is used in the control rooms of fusion energy experiments around the world. It is quintessential "e-Science" in the sense of e-Science being "computer science and information technology in the service of science". It is not, speci?cally, "Grid-enabled", but we develop it in a way that will facilitate its deployment onto the Grid. The standard version ofEScope interfaces with a specialised database for waveforms, and related data, known asMDSplus. On the acc- panying CD, we have provided you with software which will enable you to installMDSplus,EScope and sample data ?les onto Windows or Linux c- puters. There is much additional software including many versions of the case study as it gets built up and progressively refactored using design patterns. There will be a home web-site for this book which will contain up-to-date information about the software and other aspects of the case study.